Perceptions of health care providers and parents related to benefits and predisposition factors of skin-to-skin contact - Bhamani, Shelina; Syed, Areeba; Abbas, Maliha; Mitha, Hijaan; Ali, Alyza Mohammad; Hussain, Mohsina; Rashid, Aliya; Khowaja, Arisha; Naru, Tahira; Kurji, Zohra; Shaheen, Zahra; Sheikh, Lumaan (International Journal Of Community Medicine And Public Health, 2022)
Background: Skin-to-skin contact is often termed as “Kangaroo Care”. It is a method of holding a baby skin-to-skin or chest-to-chest with a parent, typically mothers. This nursing intervention helps in establishing a strong bond between a parent and a child, provides adjustment to extra-uterine life, and contributes to the holistic growth and development of the child. Moreover, Kangaroo Care is a key intervention to support the development and nurturing of preterm infants. The study aims to identify the perceptions of healthcare providers pertaining to predisposition factors and the perceived benefits of skin-to-skin contact in times of COVID-19. Methods: A cross-sectional study design was implemented in the study. The data collected from the participants attended the workshop on skin-to-skin from a wide range of health care settings (primary, secondary, and tertiary care hospitals) from Karachi, Pakistan. Results: A total of 126 health care providers participated of which 22.2% were male. Regarding predisposition factors, 112 participants agreed that skin contact enhances a mother’s love for the newborn, while 110 participants agreed that it helps the mother to take better care of the child. Additionally, 109 participants agreed that skin contact establishes an emotional bond between parents and the newborn. Conclusions: Skin-to-skin contact is one of the best and safest practices for the baby and the mother. It reduces mortality, severe illness, infection, and length of hospital stay. The evidence-based research suggests that parents and health care providers should strongly promote and implement the concept of Kangaroo Care/skin-to-skin contact.